Reflections, operational lessons, and practical insights from a pharmacovigilance inspection: a case example of organizational strategies for medical safety readiness - Tarek A. Hammad; Sasan Sabrdaran; Hesham Aboshady; Raquel Rogers; Jean-Marie Heim; Kim Bullano; Tatiana Ishida (Therapeutic Advances in Drug Safety)
Background: Pharmacovigilance (PV) inspections are critical regulatory assessments that evaluate the robustness and compliance of a company’s drug safety system. Despite their significance, there is limited published guidance on how organizations—particularly Medical Safety functions—can prepare operationally for such inspections. Objectives: To share practical, experience-based insights and organizational strategies for inspection readiness, execution, and follow-up, based on a recent large-scale European Medicines Agency PV inspection. Design: Descriptive case-based manuscript outlining the stepwise activities undertaken before, during, and after a regulatory PV inspection, with a focus on Medical Safety coordination. Methods: An internally coordinated approach was implemented, including preparatory meetings, document request management, cross-functional mock inspections, role assignments, and communication planning. A structured system was established for Medical Safety responses involving on-site and remote collaboration among safety leaders. Results: The inspection was successfully completed. The coordinated system enabled timely, consistent, and quality-controlled responses. Visual tools, including timelines and workflows, supported operational efficiency and stakeholder alignment. Post-inspection debriefs further informed process improvements across Medical Safety functions. Conclusion: This manuscript provides a practical, case-based framework for PV teams to approach regulatory inspections with strategic foresight and cross-functional coordination. The experience shared can serve as a useful reference, particularly for Medical Safety professionals and organizations seeking to strengthen inspection readiness and compliance operations.